Pensamento computacional como eixo norteador para melhorar funções neuropsicológicas de atenção e memória - Oliveira Junior, Emerson Rogério de (2024)
A challenge to be faced when seeking to maintain the healthy aging is the preservation of the neuropsychological functions of attention and memory. Due to the aging process, the more population is aging, the greater the risk of experiencing cognitive decline in these functions. Therefore, investigate and discover activities that seek to avoid or delaying problems arising from these functions becomes increasingly relevant. In this sense, the general objective of this study was to analyze the support of computational thinking in improving the neuropsychological functions of attention and memory in elderly people. The method used involved the application of a didactic sequence, structured in ten workshops, with frequency of once a week, lasting one and a half hours (90 minutes), for seven months. The pedagogical proposal was based on Piaget's constructivist theory and the activities involved the use of Scratch block programming language. Before the first workshop it was the Neupsilin test was applied, with the aim of verifying the functions neuropsychological aspects of attention and memory. Shortly after the end of the intervention, this test was reapplied, this time to verify the improvement of attention and memory functions. A third application of Neupsilin occurred six months after the second application, this time to check maintenance of the neuropsychological functions of attention and memory. Participated in the study 22 people over the age of 54. The instruments used were the MiniMental, GDS and Neupsilin. Three scientific productions were produced. The first production presents a systematic review of the literature on clinical trials involving attention and memory for elderly people with use of computerized cognitive training. The review identified that the computerized cognitive training presents gains in attention, memory, executive functions, mood, processing speed, decreased depression and improvement in the quality of life of elderly people. The second production presents the results obtained with the application of Neupsilin, with focus on memory and, as an important result, an improvement and maintenance of prospective memory of intervention participants. The third production presents the results obtained with a focus on attention, functions executive and working memory. Also, in this case, a improvement and maintenance of attention among intervention participants.